2004
DOI: 10.1158/0008-5472.can-04-1438
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Human Prostate Tumor Growth in Mice by a Cytolytic d-, l-Amino Acid Peptide

Abstract: Gene-encoded host defense peptides are used as part of the innate immunity, and many of them act by directly lysing the cell membrane of the pathogen. A few of these peptides showed anticancer activity in vitro but could not be used in vivo because of their inactivation by serum. We designed a 15-amino acid peptide, composed of D-and L-amino acids (diastereomer), which targets both androgen-independent and androgendependent human prostate carcinoma cell lines (CL1, 22RV1, and LNCaP). Most importantly, we obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(51 citation statements)
references
References 45 publications
1
49
0
Order By: Relevance
“…In addition, intratumoral administration of a cationic anticancer peptide in animal models has resulted in a long term, specific cellular immunity against the treated tumor (16). Papo et al (17,18) have demonstrated that enzymatically stable cationic peptides with a high specificity for cancer cells versus normal cells inhibit tumor growth in animal models after intravenous injections. Thus, these peptides confer a promising novel strategy for developing new anticancer agents that may overcome some of the obstacles in cancer therapy (for reviews, see Refs.…”
mentioning
confidence: 99%
“…In addition, intratumoral administration of a cationic anticancer peptide in animal models has resulted in a long term, specific cellular immunity against the treated tumor (16). Papo et al (17,18) have demonstrated that enzymatically stable cationic peptides with a high specificity for cancer cells versus normal cells inhibit tumor growth in animal models after intravenous injections. Thus, these peptides confer a promising novel strategy for developing new anticancer agents that may overcome some of the obstacles in cancer therapy (for reviews, see Refs.…”
mentioning
confidence: 99%
“…We proposed a ''CLP-assisted uptake'' mechanism to explain these traits, which may also be a general reason for the previously reported synergistic effect between other CLPs and anticancer agents. 34,35 Some recent studies using CLPs, conjugating or complexing with hydrophobic anticancer drugs as drug delivery platforms, also showed selective and fast cellular uptake of drugs, which could have a similar mechanism. 26,36 This ''therapeutic drug carrier'' strategy could provide several unique benefits.…”
Section: Discussionmentioning
confidence: 99%
“…D-K 6 L 9 is an example of cell membrane-acting peptide which triggers necrosis of cancer cells (Papo et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Introduction of d aminoacids increases stability of this peptide in other organisms as it makes proteolysis more difficult and increases peptide selectivity (Papo et al 2004). D-K 6 L 9 features both hydrophobic aminoacids (leucine) and hydrophilic ones (lysine), which make it an amphipathic molecule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation